”the regular way of trade”: Between trade and speculation in Trollope’s The Way We Live Now, 1875 and Émile Zola’s L’Argent, 1891 - Nielsen, Jakob Gaardbo (K&K - Kultur og Klasse, 2018)
This article applies a historical formalist method to analyze two literary responses to the late nineteenth-century financial sector in England and France: Anthony Trollope’s The Way We Live Now, 1875 and Émile Zola’s L’Argent, 1891. The central issue in both novels is the legal and conceptual boundary between traditional commerce and financial speculation, and the variety of ways in which established social forms and hierarchies are challenged by a rapid introduction of new forms of financial activity such as joint-stock corporations and limited liability. Both novels concern themselves with the contradictions inherent in the concept of trade and commerce in this transformed financial context, and devote critical attention to the ways in which these new forms collide in the individual lives and ambitions of its characters. Drawing on a recent theory of form by Caroline Levine, the article demonstrates how these literary representations of the accelerating financial sector should not simply be seen as reflections of an economic context in turmoil. Rather, the article argues that they apply the affordances of economic and financial forms in what is essentially an interpretative gesture, directed at the only partially visible and constantly changing reality of financial capitalism.